A prospective clinical trial of proton therapy for chordoma and chondrosarcoma: Feasibility assessment. Issue 2 (20th May 2019) - Baumann, Brian C.; Lustig, Robert A.; Mazzoni, Susan; Grady, Sean M.; O'Malley, Bert W.; Lee, John Y. K.; Newman, Jason G.; Schuster, James M.; Both, Stefan; Lin, Alexander; Dorsey, Jay F.; Alonso‐Basanta, Michelle
Abstract: Background/Objectives: Proton therapy (PRT) has emerged as a treatment option for chordomas/chondrosarcomas to escalate radiation dose more safely. We report results of a phase I/II trial of PRT in patients with chordoma/chondrosarcoma. Methods: Twenty adult patients with pathologically confirmed, nonmetastatic chordoma or chondrosarcoma were enrolled in a single‐institution prospective trial of PRT from 2010 to 2014. Seventeen patients received adjuvant PRT and three received definitive PRT. Median dose was 73.8 Gy(RBE; range 68.4‐79.2 Gy) using PRT‐only ( n  = 6) or combination PRT/intensity‐modulated radiotherapy (IMRT) ( n  = 14). Quality‐of‐life (QOL) and fatigue were assessed weekly and every 3 months posttreatment with the Functional Assessment of Cancer Therapy ‐ Brain (FACTBr) and Brief Fatigue Inventory. Primary endpoint was feasibility (90% completing treatment with < 10 day treatment delay and ≤ 20% unexpected acute grade ≥ 3 toxicity). Results: Tumors included chordomas of the skull base ( n  = 10), sacrum ( n  = 5), and cervical spine ( n  = 3), and skull base chondrosarcomas ( n  = 2). Median age was 57. The 80% had positive margins/gross disease. Median follow‐up was 37 months. Feasibility endpoints were met. The 3‐year local control and progression‐free survival was 86% and 81%. There were no deaths. Two patients had acute grade 3 toxicity (both fatigue). One had late grade 3 toxicity (epistaxis and osteoradionecrosis). There were no significant differences in patient reported fatigue or QOL from baseline to the end‐of‐treatment. Conclusions: We report favorable local control, survival, and toxicity following PRT.